Immune thrombocytopenia (ITP) World Impact Survey (I‐WISh): Impact of ITP on health‐related quality of life. Issue 2 (19th December 2020) - Cooper, Nichola; Kruse, Alexandra; Kruse, Caroline; Watson, Shirley; Morgan, Mervyn; Provan, Drew; Ghanima, Waleed; Arnold, Donald M.; Tomiyama, Yoshiaki; Santoro, Cristina; Michel, Marc; Laborde, Serge; et al.
Abstract: Immune thrombocytopenia (ITP) has a substantial, multifaceted impact on patients' health‐related quality of life (HRQoL). Data describing which aspects of ITP physicians and patients perceive as having the greatest impact are limited. The ITP World Impact Survey (I‐WISh) was a cross‐sectional survey, including 1507 patients and 472 physicians, to establish the impact of ITP on HRQoL and productivity from patient and physician perspectives. Patients reported that ITP reduced their energy levels (85% of patients), capacity to exercise (77%), and limited their ability to perform daily tasks (75%). Eighty percent of physicians reported that ITP symptoms reduced patient HRQoL, with 66% reporting ITP‐related fatigue substantially reduced patient HRQoL. Patients believed ITP had a substantial impact on emotional well‐being (49%) and 63% worried their condition would worsen. Because of ITP, 49% of patients had already reduced, or seriously considered reducing their working hours, and 29% had considered terminating their employment. Thirty‐six percent of patients employed at the time of the survey felt ITP decreased their work productivity, while 51% of patients with high/very high symptom burden reported that ITP affected their productivity. Note, I‐WISh demonstrated substantive impact of ITP on patients' HRQoL both directly for patients and from the viewpoint of their physicians. Patients reported reduced energy levels, expressed fears their condition might worsen, and those who worked experienced reduced productivity. Physicians should be aware not only of platelet counts and bleeding but also the multi‐dimensional impact of ITP on patients' lives as an integral component of disease management.